Visionary Management And Its Relationship With The Managerial Outcome - Yousof, Nur Faridatul Zaihan Md (1996)
This research examines the subordinates' perceptions towards their superiors. Visionary managers usually give a strong impact on their subordinates, therefore, it is essential to evaluate to what extent the visionary. management characteristic of managers/superiors has significant effect towards their subordinates and the organisations in general. In order to evaluate the subordinates' perceptions towards the leader and the leader's impact towards the organisation, there are 9 characteristics of the visionary management that should be analyzed.